2006
DOI: 10.1002/hyp.6213
|View full text |Cite
|
Sign up to set email alerts
|

Water storage and runoff processes in plinthic soils under forest and pasture in eastern Amazonia

Abstract: Abstract:Extensive areas of the Amazon River basin are underlain by soils with shallow impeding horizons. To evaluate how the distinctive hydraulic properties of soil with a plinthic horizon under forest and pasture affect water storage and runoff process, two first-order catchments drained by ephemeral streams were instrumental in eastern Amazonia. Field measurements showed the presence of a strong vertical gradient of saturated hydraulic conductivity, which declines to extremely low values (median <1 mm h 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
80
1
32

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(125 citation statements)
references
References 24 publications
12
80
1
32
Order By: Relevance
“…Hence, a common approach is to compare the hydrology of catchments with different land cover, but similar size, topography, soils, geology and climate (e.g. Germer et al, 2009;Moraes et al, 2006;Roa-García et al, 2011).…”
Section: E Muñoz-villers and J J Mcdonnell: Land Use Change Effmentioning
confidence: 99%
“…Hence, a common approach is to compare the hydrology of catchments with different land cover, but similar size, topography, soils, geology and climate (e.g. Germer et al, 2009;Moraes et al, 2006;Roa-García et al, 2011).…”
Section: E Muñoz-villers and J J Mcdonnell: Land Use Change Effmentioning
confidence: 99%
“…Most of our current knowledge of how Amazon land-use change influences soil hydrology and runoff generation comes from examining the effects of clearing forest for pasture production. The replacement of old-growth forest by pasture affects the hydrology of watersheds by increasing soil compaction, which in turn reduces infiltrability and hydraulic conductivity at shallow depths and shifts flowpaths from predominantly vertical towards lateral (Biggs et al, 2006;Chaves et al, 2008;De Moraes et al, 2006;Zimmermann et al, 2006). These changes have been shown to result in a longer duration and greater volumes of storm flow and greater total runoff (Germer et al, 2009;Trancoso, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Although surface runoff can occur in tropical forests (e.g. Chaves et al, 2008;Johnson et al, 2006;de Moraes et al, 2006) and was observed on paths in NF, a major contribution of surface runoff is unlikely due to high infiltration rates and hydraulic conductivity of forest soils (Owuor 30 et al, 2018). We therefore conclude that the observed signatures were caused by shallow sub-surface flow during rainfall events, which agrees with findings in NF by Jacobs et al (in review) and is commonly observed in tropical montane forested catchments (e.g.…”
Section: Dominant Water Sources 20mentioning
confidence: 99%